Give thanks for a little and you will find a lot: The role of a support seeker's reply in online support provision. Issue 2 (3rd April 2019) - Li, Siyue; Feng, Bo; Wingate, V. Skye
ABSTRACT: This experiment examined reciprocal communication among support seekers and support providers in online support forums. An interactive online support forum web page was employed where comments to a support-seeking post and a support seeker's reply to previous comments were manipulated, and participants could post their responses on the interactive web page. Results showed that support seekers received more supportive responses from subsequent viewers when they expressed appreciation for earlier comments. Compared with an appreciative reply to supportive comments, the same reply to unsupportive comments elicited more positive expectancy violations and thus higher levels of action-focused supportiveness in viewers' responses. This study extended the application of expectancy violations theory to the context of online support forums.